PRPF40A induces inclusion of exons in GC-rich regions important for human myeloid cell differentiation - Tan, Cheryl Weiqi (2024)
We characterized the regulatory mechanisms and role in human myeloid cell survival and differentiation of PRPF40A, a splicing factor lacking a canonical RNA Binding Domain. Upon PRPF40A knockdown, HL-60 cells displayed increased cell death, decreased proliferation and slight differentiation phenotype with upregulation of immune activation genes. Suggestive of both redundant and specific functions, cell death but not proliferation was rescued by overexpression of its paralog PRPF40B. Transcriptomic analysis revealed the predominant role of PRPF40A as an activator of cassette exon inclusion of functionally relevant splicing events. Mechanistically, the exons exclusively upregulated by PRPF40A are flanked by short and GC-rich introns which tend to localize to nuclear speckles in the nucleus center. These PRPF40A regulatory features are shared with other splicing regulators such as SRRM2, SON, PCBP1/2, and to a lesser extent TRA2B and SRSF2, as a part of a functional network that regulates splicing partly via co-localization in the nucleus.